(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Diaphragmatic hiatal hernia (HDH) is considered to be one of the leading diseases of the digestive system, but the exact prevalence of this condition is difficult to determine due to its often asymptomatic course and the subjectiveness of diagnostic criteria. Today, 10-15% of the world’s population suffers from cholelithiasis. However, in the Russian Federation, the number of patients suffering from gallstones in one year is 1 million, and about 500,000 people are treated surgically every year due to this disease. Along with the increase in the number of operations in gallstone disease, the number of operations that do not confuse either the patient or the surgeon is also increasing proportionally. About 10-20% of patients come to the clinic after the operation with abdominal cramps, hangovers in the upper part of the abdomen, belching, stuttering, boils in urine and a number of dyspeptic changes.